Analyzing the Effects of Innovation Strategies on Financial Performance Mediated by Contingency Variables - Mohammad Nazaripour; Amir Hossain Ranjbar (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: According to the contingency theory, the success of any organization depends on the implementation of designs tailored to the capabilities and infrastructure of that organization. Paying attention to the capabilities and infrastructure in designing innovation strategies can improve the financial performance of any organization. Therefore, this study aims to analyze the effects of innovation strategies on financial performance mediated by contingency variables such as human capital, structural capital, customer capital, management accounting information systems, internal process performance, and customer performance.Methodology: The present study is practical and considered a descriptive-exploratory correlation study. The required data were collected through a questionnaire. The statistical population of the present study is the manufacturing companies of Hamadan. Regression and structural equation modelling were used to test the hypotheses and analyze the data. SPSS and SmartPLS software were also used to analyze the data.Findings: Innovation strategies positively and significantly affect financial performance. Contingency variables (human capital, structural capital, customer capital, management accounting information systems, internal process performance, and customer performance) positively and significantly affect the relationship between innovation strategies and financial performance, meaning these variables explain and mediate part of this relationship. The research findings indicate that the demographic variables of gender, age, education, field of study, years of service, and type of industry do not significantly affect financial performance.Originality/Value: Since the companies' going concern depends on their successful financial performance, innovation strategies through improving financial performance can play a significant role in the companies' going concern.